Antiproliferative, antimetastatic properties of phyllanthus specieson breastand lungcancer cell linesand their targetted signal transduction pathways / Lee Sau Har - Lee, Sau Har (2013)

(untitled)
Cancer is the second leading cause of death worldwide and among them, lung and breast cancers have mortality rates of 1.4 million and 400,000 deaths each year respectively. This is due to the current chemotherapies that are still far from ideal and hence, alternative treatments founded in a ‘back-to-nature’ approach might yield improved treatment avenues. The genus Phyllanthus is a rainy season weed that has been exploited for various medicinal usages due to the presence of abundant polyphenol compounds in the plant that can be broadly grouped into ellagitannins, gallotannins, flavonoids, and phenolic acids. Therefore, the aim of the current study was to evaluate the antimetastatic potential of four Phyllanthus species (P. niruri, P. urinaria, P. watsonii, and P. amarus) on lung (A549) and breast (MCF-7) carcinoma cell lines. Phyllanthus exhibited antiproliferative activity by causing selective toxicity on A549 and MCF-7 cells with IC50 values ranging from 50-470g/ml, without the involvement of cell cycle arrest. At these IC50 concentrations, Phyllanthus successfully halted the endothelial-mesenchymal transition process by increasing cell aggregation and cell-cell adhesion. Phyllanthus also reduced the invasion of A549 and MCF-7 cells through the extracellular matrix layer by 40% and 10%, respectively. It was also observed that Phyllanthus inhibited almost 60% cells adhesion to the matrix layer while suppressing up to 80% migration of these cells through an 8μm pore size polycarbonate membrane. This ability of Phyllanthus to inhibit A549 and MCF-7 cells’ invasion, migration, and adhesion were even enhanced at increasing treatment concentrations and were associated with their capacity to repress the expressions of matrix metalloproteinases 2, 7, and 9 in cancer cells that function to hydrolyze the basement membrane during cell metastasis. In addition, Phyllanthus induced apoptosis in A549 iv and MCF-7 cells in conjunction to its antimetastatic action with the activation of caspases-3 and -7 as well as DNA fragmentation. Among the four Phyllanthus species, P. urinaria inhibited cancer cells growth and metastasis most effectively, closely followed by P. watsonii. Following this, we screened the ten major cellular signaling pathways and recognized that Phyllanthus exerted its antimetastatic and apoptosis-inducing activities by inhibiting ERK1/2 and hypoxia pathways, attributed to the repression of signaling transduction components such as G proteins, G protein receptors, and serine/threonine-protein kinases. ERK1/2 pathway inhibition by Phyllanthus subsequently led to downregulated expression of cytoskeletal proteins for cell invasion and mobility, protein synthesis and transcriptional proteins for cell growth, as well as antiapoptotic protein for cell survival. Meanwhile, inhibition of the hypoxia pathway repressed expression of angiogenic proteins that are essential for cell angiogenesis and migration as well as various glucose uptake and glycolytic enzymes for cell growth and metabolism. Phyllanthus also suppressed drug detoxification enzymes and tumor defense mechanism proteins including gluthathione transferase, gluthathione synthetase, metallothionein, and annexins. In summary, Phyllanthus could be a valuable candidate as a therapeutic agent for metastatic cancers since it does not only stop spreading of cancer cells, but it also inhibits cell growth and induces apoptosis.